MEMBANGUN KARAKTER GENERASI MUDA MELALUI NILAI RITUAL METRI - Rahmawati Mulyaningtyas; Yogi Dian Arinugroho (PUSAT MPK UNIVERSITAS BRAWIJAYA, 2020)
The Building of Youth Character Trough Metri Ritual Value. The salvation ritual or it is so called metri in Ringinpitu Village still exists and goes on. The values contained in the ritual of metri can be used as a means to build the worthy character of the youth generation. This study uses descriptive qualitative method. Data were obtained from the results of interviews and literature review. Interviews were conducted with the elders of Ringinagung Subvillage, Ringinpitu Village, , Tulungagung Regency. The results of this study reveal that there are philosophical and religious values in ritual of metri in Ringinpitu Village. These values are contained in the ijab (speech / prayer of the leader of metri ritual) and the special dishes prepared. Worthy characters that can be built from metri rituals are mutual cooperation, cooperation, harmony, always remembering God, and always remembering the merits of the predecessors or ancestors.